(untitled) - Wright, Sharon Saltzgiver (Hoboken, NJ, 2003)
Everything you need to know about bonds Bonds are a key component in every portfolio, making it essential that investors understand what exactly they are and how they function. Getting Started in Bonds, Second Edition has been fully updated and revised to take into account the ever-changing bond market as well as the current economic environment. This new edition explains the fundamentals of bonds in clear, easy-to-understand language. It includes in-depth coverage of a variety of debt products, from Treasury notes to high-yield junk bonds and everything in between. This comprehensive guide is an essential primer for anyone who would like to invest in bonds but doesn't know where to start.
Keywords: Bonds,Trái phiếu